(untitled) (Clinics, 2021)
OBJECTIVES: To compare the inflammatory and oxidative stress (OS) states of adults with bronchiectasis with those of healthy controls and correlate inflammatory and OS levels with lung function and physical capacity. METHODS: This study used a cross-sectional design. Seventy-four adults with bronchiectasis (age: 49±15 years, forced expiratory volume in 1 second [FEV1]: 52.5±25.6%) and 42 healthy controls (age: 44±17 years, FEV1: 95.9±14.0%) performed cardiopulmonary exercise tests and incremental shuttle walking tests. Their physical activity in daily life, inflammatory cytokine, and antioxidant levels in plasma were measured. RESULTS: Compared to that of the controls, the levels of interleukin (IL)-6 (po0.001), IL-10 (po0.001), carbonylated proteins (p=0.001), and superoxide anions (p=0.046) were significantly increased in adults with bronchiectasis. Catalase activity was also reduced in this group (po0.001). The inflammatory markers IL-1b, IL-6, and tumor necrosis factor-a correlated negatively with aerobic capacity (r=-0.408, r=-0.308, and r=-0.207, respectively). We observed similar correlations with OS markers (thiobarbituric acid and carbonyls; r=-0.290 and r=0.379, respectively), and these markers also significantly correlated with the aerobic capacity. CONCLUSIONS: Adults with bronchiectasis presented an increased systemic inflammatory response that correlated negatively with physical capacity.